2018
DOI: 10.1088/1748-9326/aaa0b4
|View full text |Cite
|
Sign up to set email alerts
|

Are Scots pine forest edges particularly prone to drought-induced mortality?

Abstract: Climate change is expected to exacerbate the frequency of drought-induced tree mortality world-wide. To better predict the associated change of species composition and forest dynamics on various scales and develop adequate adaptation strategies, more information on the mechanisms driving the often observed patchiness of tree die-back is needed. Although forest-edge effects may play an important role within the given context, only few corresponding studies exist. Here, we investigate the regional die-back of Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
111
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(123 citation statements)
references
References 61 publications
(39 reference statements)
9
111
0
3
Order By: Relevance
“…Thus, it can be concluded that the drought conditions of the summer season are the main climatic driver affecting the radial growth of Scots pine provenances. These results are consistent with recent studies on Scots pine, regardless of the study region (e.g., [86][87][88][89]). An additional climatic factor crucial to initiating growth activity is the temperature of the month preceding the growing season (March, Figure 6A).…”
Section: Climate-driven Between-provenance Variationsupporting
confidence: 93%
“…Thus, it can be concluded that the drought conditions of the summer season are the main climatic driver affecting the radial growth of Scots pine provenances. These results are consistent with recent studies on Scots pine, regardless of the study region (e.g., [86][87][88][89]). An additional climatic factor crucial to initiating growth activity is the temperature of the month preceding the growing season (March, Figure 6A).…”
Section: Climate-driven Between-provenance Variationsupporting
confidence: 93%
“…In addition to temperature, moisture availability has also been documented as a growth-limiting factor (RW: Helama and Lindholm, 2003;Vitas, 2004Vitas, , 2006Erlickytė and Vitas, 2008;Drobyshev et al, 2011;Düthorn et al, 2013;Bose et al, 2020;RW and EBI: Seftigen et al, 2020). At the southern distribution margin, plant water availability (RW: Bogino et al, 2009;Buras et al, 2018a), precipitation (RW: Sánchez-Salguero et al, 2015a), and winter, spring, or summer temperatures (RW: Herrero et al, 2013;Sánchez-Salguero et al, 2015a,b) modulate Scots pine growth.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cost of reproduction may vary at the individual scale due to differences in stored reserves or access to belowground resources. Individualistic growth responses to climate have previously been investigated using tree rings (Carrer, 2011;Buras et al, 2018), but the potential for these to be driven by individualistic responses to reproduction remains underexplored.…”
Section: Introductionmentioning
confidence: 99%